Reconstruction of Urban Forests post World War II and the Bosnian War - McBride, Joe R.; Stilgenbauer, Judith; Lacan, Igor; Cheng, Sheauchi; Medbury, Scot; McBride, Deborah L. (Springer, 2021)
This book will address the destruction of urban forest in nine cities by bombing during World War II and the Bosnian War and their reconstruction in the post-war years. After reviewing the general objectives and results of aerial bombing, the book explores the effects of bombing and the reconstruction of urban forest in London, Coventry, Hamburg, Dresden, St. Petersburg, Stalingrad, Tokyo, Hiroshima, and Sarajevo. Sarajevo stands out among these cities because the destruction of its urban forest was the result of citizens cutting down trees for firewood during the siege of the city. Most of the cities studied developed plans for reconstruction either during or after the war. These plans often addressed the planning and re-establishment of the urban forest that had been destroyed. Urban planners often planned for infrastructure improvements such as new boulevards and parks where trees would be planted. After the war many of these plans were abandoned or significantly modified.